PERANCANGAN UI/UX APLIKASI PEMBELAJARAN BAHASA JEPANG MENGGUNAKAN METODE GOAL DIRECTED DESIGN - Oka Mochamad Ocktafian Setiadi; Imam Maruf Nugroho; Yusuf Muhyidin (PROGRESS, 2023)
Japanese language learning has been available at SMAN 2 Purwakarta since 2005. Students of SMAN 2 Purwakarta have difficulty learning Japanese due to the lack of variety in class. So researchers took the initiative to design a Japanese learning application. User Interface (UI) is a design before the creation of applications that focuses on visuals and product elements such as colors, layouts, buttons and typography. User Experience (UX) is the experience of a user when using an application. UI and UX have an important role in the problems that exist at SMAN 2 Purwakarta because they can add new innovations to Japanese language learning. Goal Directed Design is the method used in this study because it focuses on goals and user experience. The test method used is the System Usability Scale to find the average value of the final results for the application design made.